PENGARUH MOTIVASI BELAJAR DAN SIKAP BELAJAR TERHADAP PRESTASI BELAJAR BAHASA INDONESIA SISWA MTS - Nurhasanah, Nurhasanah; Mering, Aloysius; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study examines the influence between motivation (X1) and learning attitudes (X2) individually or together to the variable of learning achievement (Y). The hypothesis of this research is (1) There is a positive influence of learning motivation of learners to the achievement of learning Indonesian class VII students MTs in South Singkawang lesson year 2016/2017. (2) There is a positive influence of learning attitude pesertdidik with learning achievement of Indonesian students class VII MTs in South Singkawang academic year 2016/2017 (3) There is a positive influence of motivation and learning attitudes of learners together with the achievement of learning Indonesian class VII students MTs Singkawang Selatan lesson year 2016/2017. The samples of the study were taken entirely because the number of students was only 84 people then, thus this study was population research. The regression equation to be tested was Regression of Three Predictors Y = a + b1 X1 + b2 X2. From the analysis proved (1) The magnitude of the effect of motivation variables with learning outcomes are categorized as high as 0.735. This means there is a meaningful influence between the motivation of learning with student learning outcomes. (2) The amount of influence of attitude variables with learning outcomes are categorized as high as 0.663. This means that there is a significant influence between learning motivation and student learning outcomes. (3) Fh value of ANOVA table is 64.462> Ft (3.109) then Ho is rejected and Ha accepted. That is, motivation and learning attitudes affect the student learning outcomes. From the research results suggested for other researchers who want to study this research further, should consider some factors that affect the motivation and attitudes of students to learning Indonesian language because the motivation and attitude between students with one another. Keywards : Effect Of Learning and Attitude Motivation To Student Learning Achievement